A survey on OAUTH protocol for security - Srikanth, V; Sneha Latha, Jupalli; Ajay Kumar, Dinne; Uma Maheswari, Kakarla (International Journal of Engineering and Technology, 2017)
Web is a dangerous place. For each administration, each APIâ€™s, there are clients who might love simply to get through the different layers of security you've raised. It is one of the most powerful open standard authorization protocols available to all API developers today. Most of the popular social network APIâ€™s like Google, Twitter and Facebook uses OAuth 2.0 protocol to intensify user experience while sign-ing-on and social sharing. The code written for authorization may be leaked during transmission which then may lead to misuse. This paper uses an attacker model to study the security vulnerabilities of the OAuth protocol. The experimental results on Google API shows that some common attacks like Phishing, Replay and Impersonation may be possible on this protocol.Â